Canal wall window tympanomastoidectomy A review of 84 cases (Bangladesh Journal of Otorhinolaryngology, 2010)
Canal wall window (CWW) tympanomastoidectomy is a modified form of attico-antrostomywhich can be a substituted for canal wall down procedure. A retrospective study of 84 casesof CWW tympanomastoidectomy were collected from department of otolaryngology and Headnecksurgery, BSMMU and ENT Foundation Hospital, Dhaka from June 2005 to July 2009.In this study majority of the patients were 16 to 48 years 57(67.86%). Male female ratio was3:1. Most of the patients were found cholesteatoma 27 (32.14%), granulation tissue 25(29.76%),retraction pocket 22(26.19%),Postoperative hearing gain (mean three frequency pure tone air bone gap) assessed 3 monthsafter primary surgery, most of the patients 34(40.48%) had gain 20dB+, 26 patients (30.95%)had gain 10dB+,18 patients (2143%) had gain 30dB+.Materials used in tympano-ossiculoplasty were chonchal cartilage, sculptured incus, PORPand TORP. Most of the patients we used incus reposition 36(42.86%), cartilage ossiculoplasty28(33.33%), PORP 12(14.29%) and TORP 8 (9.52%).Post operative followup of the patient was done in 1 month, 3 month and 6 month intervals andcondition of external auditory canal assessed. Dry ear were found 70 patients (83.33%), moistear were found 8 patients (9.52%) and 6 patients (7.14%) were found purulent dischargingears and later canal wall down mastoidectomy done .Key words: Canal wall window; Tympanomastoidectomy.DOI: 10.3329/bjo.v16i1.5774Bangladesh J Otorhinolaryngol 2010; 16(1): 3-8